Improving Islamic Financial Literacy of Students of PPMTI Tanjung Berulak through a Participatory Education Program Based on Counseling - Mifta Hasda; Saru Reza; Hidayat Hidayat; Zubaidah Assyifa; Muhammad Arif (Global Sustainability Research Institute, 2026)
This community service activity was carried out at the Madrasah Tarbiyah Islamiah Islamic Boarding School (PPMTI) Tanjung Berulak with the theme